TINJAUAN HUKUM DAN ETIKA TERHADAP PENANGGUHAN PELAYANAN ESSENSIAL DI RUMAH SAKIT - Putu Sarjana; Chepi Ali Firman Zakaria; Tono Hadi Susiarno (Masyarakat Hukum Kesehatan Indonesia, 2022)
The suspension of essential healthcare services during the COVID-19 pandemic has raised ethical and legal considerations. This article provides a review of the legal and ethical aspects that should be considered when deciding to delay healthcare services deemed non-urgent. The legal aspect to consider is the patient's right to adequate healthcare and the right to receive clear and accurate information about their health condition, as well as the right to choose medical treatments. Delaying essential services can be done to control the spread of the virus and protect patients and healthcare workers, but must be done carefully and in accordance with ethical principles. Hospitals must consider factors such as patient needs, hospital capacity, and resource availability before delaying essential services. It is also important for hospitals to communicate clearly and accurately with patients about the decision to delay essential services and provide safe alternatives for care or treatment delays. When suspending essential services, hospitals must consider the legal and ethical aspects to ensure that patient rights are respected and that adequate healthcare services remain available.